Spatial Policies and Land Use Patterns: Optimal and Market Allocations - Efthymia Kyriakopoulou; Anastasios Xepapadeas (Fondazione Eni Enrico Mattei (FEEM), 2014)
We study the optimal and equilibrium distribution of industrial and residential land in a given region. The trade-off between the agglomeration and dispersion forces, in the form of pollution from stationary forces, environmental policy, production externalities, and commuting costs, determines the emergence of industrial and residential clusters across space. In this context, we define two kinds of spatial policies that can be used in order to close the gap between optimal and market allocations. More specifically, we show that the joint implementation of a site-specific environmental tax and a site-specific labor subsidy can reproduce the optimum as an equilibrium outcome. We also propose a novel approach that allows for endogenous determination of land use patterns and provides more precise results compared to previous studies.
Keywords: R14; R38; H23; 330; Spatial Policies; Agglomeration; Land Use; Pollution; Environmental Tax; Labor Subsidy